Strategi Kolaboratif Aparat dan Masyarakat dalam Pemberantasan Narkoba di Bima NTB - Wahyudi; Herman (Universitas Hamzanwadi, 2026)
This study aims to analyze the implementation, challenges, and effectiveness of collaborative strategies between law enforcement agencies and local communities in combating drug problems at the local level. This research adopts a collaborative governance approach, emphasizing cross-sector cooperation among state institutions, local governments, religious leaders, traditional figures, and community members in addressing complex social problems collectively. Employing a qualitative descriptive approach with a case study design, data were collected through in-depth interviews with law enforcement officers, community and religious leaders, village officials, focus group discussions with residents, and analysis of policy documents and official reports. The findings reveal that collaborative strategies have been implemented through community-based prevention programs, joint law enforcement operations, and limited rehabilitative efforts.These collaborations have contributed to increased public awareness and improved effectiveness of drug law enforcement. However, the study also identifies critical challenges, including indications of drug trafficking syndicates involving rogue law enforcement officers, public apathy and weakened social control, and the suboptimal role of religious leaders in social regulation. These challenges undermine public trust and limit community participation, which are essential for sustainable collaboration. This study addresses a research gap in previous studies that predominantly focused on statistical trends, legal enforcement, or general drug prevention programs without comprehensively examining the dynamics of collaborative governance at the local level, particularly in Kabupaten Bima.